Delivering water security in a changing world - Howard S. Wheater (The UNESCO Courier, 2019)
Eighty per cent of the world's population is exposed to high levels of threats to water security and a severe water crisis is looming by 2070. Faced with these alarming estimates, the author argues that a business-as-usual attitude will not work. Water management is a scientific issue, but it is also a matter of politics, governance and societal values. A new transdisciplinary science is urgently needed.